Designing a Web-Based Inquiry Management Platform Using a Design Thinking Approach: Case Study : PQM Consultants - Nindytha Salsabila; Astri Ghina (International Journal of Economics, Commerce, and Management, 2025)
Technological advancements and digital transformation have significantly impacted business management, including the consulting sector. PQM Consultants faces challenges in managing inquiries, which are still manually handled using Microsoft Excel. This manual process results in fragmented data, delays in accessing information, input errors, and difficulties in real-time monitoring of inquiry statuses. These issues affect operational efficiency, data transparency, and timely decision-making. This research focuses on developing a web-based inquiry management platform through the Design Thinking methodology, aiming to improve the efficiency and effectiveness of inquiry handling at PQM Consultants. Adopting a qualitative case study approach, the study gathers insights through in-depth interviews, direct observations, and document reviews involving consultants and support team members who are directly engaged in the inquiry process. Research participants consist of consultants and support team members directly involved in inquiry management. The study uses a Design Thinking approach, which focuses on solving problems through repeated refinement and actively involving users throughout the development process. This framework supports the development of creative solutions by deeply understanding user needs, defining key challenges, and continuously refining ideas through prototyping and testing (Costich 2021). The Empathize stage focuses on understanding user needs and challenges. The Define stage formulates the core problems specifically. The Ideate stage generates creative ideas as potential solutions. The Prototype stage develops an initial design of the platform, which is then tested during the Test stage to gather feedback for further refinement. The results indicate that the web-based inquiry management platform effectively addresses various challenges in managing inquiry data, such as access delays, input errors, and data fragmentation. The platform enables consultants to monitor inquiry statuses in real-time, access data transparently, and make faster and more accurate decisions.